2016
DOI: 10.1007/s00248-016-0754-4
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco, Microbes, and Carcinogens: Correlation Between Tobacco Cure Conditions, Tobacco-Specific Nitrosamine Content, and Cured Leaf Microbial Community

Abstract: Tobacco-specific nitrosamines are carcinogenic N-nitrosamine compounds present at very low levels in freshly harvested tobacco leaves that accumulate during leaf curing. Formation of N-nitrosamine compounds is associated with high nitrate levels in the leaf at harvest, and nitrate is presumed to be the source from which the N-nitrosation species originates. More specifically, nitrite is considered to be a direct precursor, and nitrite is linked with N-nitrosation in many environmental matrices where it occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 32 publications
4
23
0
Order By: Relevance
“…Obviously then, the levels of TSNAs in ST products differ not only as function of total microbial load but probably also as a function of microbial community composition. Indeed, a very recent study has found the TSNA concentrations in tobacco leaves to correlate positively with the proportions of Firmicutes and inversely with those of Proteobacteria [20]. Interestingly, Firmicutes was the predominant phylum in the American, Sudanese and Yemeni products in this study, while…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Obviously then, the levels of TSNAs in ST products differ not only as function of total microbial load but probably also as a function of microbial community composition. Indeed, a very recent study has found the TSNA concentrations in tobacco leaves to correlate positively with the proportions of Firmicutes and inversely with those of Proteobacteria [20]. Interestingly, Firmicutes was the predominant phylum in the American, Sudanese and Yemeni products in this study, while…”
Section: Discussionsupporting
confidence: 43%
“…Early reports, mostly by investigators of the tobacco industry, performed identification and quantification of bacteria and fungi in fresh and processed tobacco, using cultivationbased methods [15]. Recently, 16S rRNA-based techniques including random fragment length polymorphism (RFLP), denaturing gradient gel electrophoresis (DGGE), single strand conformation polymorphism (SSCP) and sequencing have been used to characterize bacterial communities in fresh and cured tobacco leaves as well as those associated with tobacco fermentation process [16][17][18][19][20]. These studies revealed great deal of diversity and differences in the composition of microbiota associated with the different forms of tobacco.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the members of the core microbiome were also present in the core microbiome defined for air-cured burley tobacco including Pantoea , Pseudomonas , Sphingomonas , and Bacillus (Law et al, 2016). Despite this agreement in core members between products, our results showed there was some divergence in bacterial community composition between brands of cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…This is suggested to be, in part, due to certain nitrate and nitrite reducing bacterial species present on or in the tobacco leaves (Atawodi and Richter, 1996). High temperatures and relative humidities have been shown to be key factors that contribute to increasing levels of TSNAs throughout curing (Burton et al, 1989b; Law et al, 2016) and storage (Burton et al, 1989a; Shi et al, 2013) of tobacco. TSNA levels in smokeless tobacco brands have also been shown to be influenced by storage conditions, with high levels of TSNAs associated with storage for 4 weeks at room and high temperatures (>37°C), but not low temperature (4°C; Djordjevic et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Early reports, mostly by investigators of the tobacco industry, performed identification and quantification of bacteria and fungi in fresh and processed tobacco using cultivation-based methods [15]. Recently, 16S rRNA-based techniques including random fragment length polymorphism (RFLP), denaturing gradient gel electrophoresis (DGGE), single strand conformation polymorphism (SSCP), and sequencing have been used to characterize bacterial communities in fresh and cured tobacco leaves as well as those associated with tobacco fermentation process [16,17,18,19,20]. These studies revealed great deal of diversity and differences in the composition of microbiota associated with the different forms of tobacco.…”
Section: Introductionmentioning
confidence: 99%